Study on the effect of baking process on the quality characteristics, moisture distribution and sensory evaluation of bran, duck and pork emulsification sausage - Shang, Feifei; Kryzhska, Tetyana; Duan, Zhenhua (Eastern-European Journal of Enterprise Technologies, 2022)
Poultry sausage is a low-fat, protein-friendly product, and the research on poultry sausage has gradually become a hot field of meat product research. The baking process can promote the decomposition of protein and fat, and the Maillard reaction occurs, thereby increasing the color of the sausage and improving the flavor of the sausage. Baking time affects cooking loss, color, pH, TPA, moisture distribution and sensory evaluation results of cooked sausage products, therefore, the baking process is very important. In this study, four baking treatment experiments of 40, 60, 80 and 100 min were set up, the baking temperature was 60 °С. The 60min treatment group had the smallest brightness value L, the highest redness value a, and the best color. The water content of the 40 min treatment group was the highest, followed by the 80 min treatment group, and the pH value of the other 80 min treatment group was also the lowest. In terms of TPA and water distribution, the hardness value of the 60 min treatment group was the highest, and the relaxation times (T2) corresponding to hydrated water, fixed water and free water were 0.1‑9.3 ms, 10‑91 ms, and 175‑900 ms, respectively, and the 80 min treatment group The group with the most semi-bound water worked best. In terms of sensory evaluation, the color, flavor, texture, and overall acceptability of the 60‑80 min treatment groups were not significantly different. The best evaluation result was the 100 min treatment group, followed by the 60 and 80 treatment groups. Based on the above research results of sausage quality, the optimal baking time of sausage in this study is 60‑80 min. This research can provide product quality data and technical support for the development of duck and pork compound sausages.